Specific detection of Bradyrhizobium and Rhizobium strains colonizing rice (Oryza sativa) roots by 16S-23S ribosomal DNA intergenic spacer-targeted PCR. - Tan, Zhiyuan; Hurek, Thomas; Vinuesa, Pablo; Müller, Peter; Ladha, Jagdish K.; Reinhold-Hurek, Barbara (American Society for Microbiology, 2001)
In addition to forming symbiotic nodules on legumes, rhizobial strains are members of soil or rhizosphere communities or occur as endophytes, e.g., in rice. Two rhizobial strains which have been isolated from root nodules of the aquatic legumes Aeschynomene fluminensis (IRBG271) and Sesbania aculeata (IRBG74) were previously found to promote rice growth. In addition to analyzing their phylogenetic positions, we assessed the suitability of the 16S-23S ribosomal DNA (rDNA) intergenic spacer (IGS) sequences for the differentiation of closely related rhizobial taxa and for the development of PCR protocols allowing the specific detection of strains in the environment. 16S rDNA sequence analysis (sequence identity, 99%) and phylogenetic analysis of IGS sequences showed that strain IRBG271 was related to but distinct from Bradyrhizobium elkanii . Rhizobium sp. ( Sesbania ) strain IRBG74 was located in the Rhizobium - Agrobacterium cluster as a novel lineage according to phylogenetic 16S rDNA analysis (96.8 to 98.9% sequence identity with Agrobacterium tumefaciens; emended name, Rhizobium radiobacter ). Strain IRBG74 harbored four copies of rRNA operons whose IGS sequences varied only slightly (2 to 9 nucleotides). The IGS sequence analyses allowed intraspecies differentiation, especially in the genus Bradyrhizobium, as illustrated here for strains of Bradyrhizobium japonicum, B. elkanii, Bradyrhizobium liaoningense, and Bradyrhizobium sp. ( Chamaecytisus ) strain BTA-1. It also clearly differentiated fast-growing rhizobial species and strains, albeit with lower statistical significance. Moreover, the high sequence variability allowed the development of highly specific IGS-targeted nested-PCR assays. Strains IRBG74 and IRBG271 were specifically detected in complex DNA mixtures of numerous related bacteria and in the DNA of roots of gnotobiotically cultured or even of soil-grown rice plants after inoculation. Thus, IGS sequence analysis is an attractive technique for both microbial ecology and systematics.